Seven decades of shoreline changes along a muddy mangrove coastline of the Upper Gulf of Thailand. Issue 6 (1st February 2022) - Sok, Kimhuy; Bidorn, Butsawan; Burnett, William C.; Sasaki, Jun; Sola, Phachirarat
Abstract: This study evaluates the historical coastal change and development along the eastern coastline of the Upper Gulf of Thailand between 1953 and 2019 based on a series of aerial photographs and satellite images. Long‐term (~70 years) and short‐term (~10 years) shoreline movement rates were analysed using the Digital Shoreline Analysis System (DSAS). Results of this analysis indicate that the shoreline along the western coast (WBK) of the Bang Pakong River mouth has undergone severe coastal degradation, with a land loss of about 980 ha over the last seven decades. Meanwhile, the eastern coastline (EBK) has developed continuously over this time span, resulting in a land growth of about 552 ha. Based on historical shorelines recorded since 1954, the shoreline recession along the WBK coast accelerated over five decades. The average shoreline change rate reached approximately −9 m/year in 2002 and is shown to be related to land subsidence, which was due to groundwater withdrawals. The WBK coastline stabilized in 2009 and became an accretionary coast after 2016 due to the introduction of engineered coastal protection measures. In addition, the construction of major dams on the Chao Phraya and Bang Pakong rivers did not result in severe shoreline recession along the WBK coast. A significant reduction in sediment supply to the coastal zone due to damming was not observed. In contrast, the EBK coastline has advanced continuously since 1953, with average growth rates between 0.5 and 7.6 m/year over 50 years as a result of increased riverine sediment supply. Our results also indicate that mangrove deforestation was not a major factor causing shoreline retreat, and mangrove reforestation was not a successful coastal protection approach in this coast. Abstract : We show that the western coastline of the Bang Pakong River, a part of the Eastern Economic Corridor Project, one of the largest economic hubs in Asia, has experienced severe shoreline retreat (among the highest in the world) due to groundwater pumping. Meanwhile, the eastern coastline has been naturally expanding seaward due to an increase in riverine sediment supply. Moreover, mangrove deforestation was not the main cause of shoreline retreat, and mangrove reforestation did not successfully protect the eroded coastline.